Induction of Somatic Embryogenesis of Pontianak Siamese Orange Cotyledon Cultures on Murashige Skoog Media with the Addition of 2,4-D and Kinetin - Zakiah, Zulfa; Turnip, Masnur (Jurnal Biologi Tropis, 2024)
Conventional citrus propagation has weaknesses, one of which is susceptible to CVPD(Citrus Vein Phloem Degeneration) and other diseases which are the main cause of the decline in population and production of pontianak siam orange plants in West Kalimantan. One alternative to in vitro propagation of citrus seedlings is the induction of somatic embryogenesis. The purpose of the study was to obtain the best combination of 2,4-D and kinetin concentrations for callus induction and somatic embryo induction from Pontianak siam orange cotyledon explants, observing the developmental phase (stage) of embryos formed. The implementation of the study used a factorial completely randomized design (CRD) consisting of 2 factors. The first factor is the concentration of 2,4-D consisting of 4 concentration levels, namely 0; 0.5; 1; 1.5; 2 mg/L. The second factor is kinetin concentration consisting of 4 concentration levels, namely 0; 0.5; 1; 1.5; 2 mg/L.The observation parameters include the time of callus emergence (hst), the percentage of explants forming callus (%), the texture and color of the callus, observing the stage of the embryo found. The results showed that 72% of treatments were able to induce callus from pontianak siam orange cotyledons with an average callus appearance at 7 hst. The callus formed is compact and crumbly with varied callus colors, namely white, yellowish, greenish and brownish. The best treatment that produces embryogenic callus is the combination of D0.5K0.5; D1K1; D0.5K1.5; D1.5K1.5 and D2K2 with the characteristics of crumbly callus and yellowish and brownish colors. The results of microscopic observations found that the somatic embryo phase formed was the pro-embryo phase.